Dramaturgy: Riba on Home Ownership Loan in Islamic Banking (Case Study on Bank BTN Syariah KCPS Ciputat, Tangerang Selatan) - Aulia Julian Faizatunazilla; Siti Jamilah (BASKARA : Journal of Business and Entrepreneurship, 2020)
The purpose of this study was to determine usury behavior in the Housing Loan or Credit in Islamic banks and to determine the application of the existing contract system in Housing Loans in Islamic banks using the dramaturgy method. The data used in this study is primary data, where researchers conducted interviews directly with the Bank BTN Syariah KCPS Ciputat, a member of the Sharia Supervisory Board and one of the customers who used a House Ownership Credit product at an Islamic bank. The results of this study can be concluded that the front stage that the bank shows to the public is in accordance with the back stage that the bank does not show to the public and Bank BTN Syariah KCPS Ciputat conducts its business in accordance with Islamic law and the fatwa of the National Sharia Council. So that in this study Bank BTN Syariah KCPS Ciputat does not have usury in its business.